A pricing model to optimize the promotions period in airlines (2016)
Promotions are a common practice used by the airline industry to increase the passenger demand. There are two important decisions that need to be taken into account before performing a promotion: (1) estimate the discount dates and (2) the price of the ticket. To estimate this, several key variables are taken into account. First is the demand because it represents the perception and response to changes on the product. This is fundamental when defining the duration of a promotion. Throughout this article we will present a dynamic programming model that determines when it is optimal to perform a promotion, in other words when to start it and for how long. For robustness, we used data from the airline industry and evaluated the model for two cases. The results were coherent and behaved as expected. Our results show that there should be a promotion when the expected normal demand is not sufficient and the dilution costs are not higher than the incremental revenue.